Stress Level Response of Nursing Students to Online Learning During the Covid-19 Pandemic - Sujiah Sujiah; Dewi Yuliana (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
The Covid-19 pandemic has caused crises in various aspects, including in education. To resolve it, the Indonesian government shifted the face-to-face learning method to the online learning method. Online learning is one of the solutions to teaching and learning during the Covid-19 pandemic. This change causes the need for adaptation for students. The inability of students to adapt to the makes them stressed. This study aimed to determine the stress level response of the three-semester undergraduate nursing student with online learning during the Covid-19 pandemic. This study uses a quantitative descriptive design. The population in this study were all active undergraduate nursing students in the 3rd semester of Mitra Indonesia University as many as 114 students, with a research sample of 72 students taken by simple random sampling technique with the Lemeshow formula. The validity test results showed that the questionnaire was valid with a Pearson’s correlation value of=0,3 reliable with Cronbach’s alpha of=0,8. The collected data were analyzed using descriptive statistics. The results of this study that 20,8% respondents (n=15; 20,8%) who normal stress, mild stress 4 respondents (n=4; 5,6%), moderate stress (n=16; 22,2%), while the respondents who feel they are experiencing severe stress (n=17; 23,6%), and very severe stress there are (n=20; 27,8%). Conclusions: Based on the results of this study, it was concluded that 27,8% of students felt very severe stress by online learning during the Covid-19 pandemic.